Penerapan Metode Promethee Sebagai Sistem Pendukung Keputusan Pemeringkatan Siswa - Watrianthos, Ronal; Kusmanto, Kusmanto; Simanjorang, Elida F. S.; Syaifullah, Muhammad; Munthe, Ibnu Rasyid (STMIK Budi Darma, 2019)
Students rank requires several considerations and criteria. Determination of the criteria must be prepared as much as possible because it is related to the selection of outstanding students. However, this ranking is considered less than optimal and requires a long time because it is processed manually by the school. The right Decision Support System is needed to produce quick and accurate ranking decisions. This study uses the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) as a Decision Support System. This method will use multi-criteria as the main input in decision making. PROMETHEE will be used to analyze criteria based on alternatives compared to rank according to students' grades and abilities. Based on the research sample data, the highest value was 0.739 for alternative A16. This shows that alternative A16 is the best alternative compared to other alternatives based on consideration of all criteria. The development of PROMETHEE with application-based Decision Support Systems is much better because it produces fast and accurate calculations.